2019
DOI: 10.3390/s19163480
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fast E-nose System for Early-Stage Diagnosis of Aphid-Stressed Tomato Plants

Abstract: An electronic nose (E-nose) system equipped with a sensitive sensor array was developed for fast diagnosis of aphid infestation on greenhouse tomato plants at early stages. Volatile organic compounds (VOCs) emitted by tomato plants with and without aphid attacks were detected using both the developed E-nose system and gas chromatography mass spectrometry (GC-MS), respectively. Sensor performance, with fast sensor responses and high sensitivity, were observed using the E-nose system. A principle component analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Plant VOCs also affect the food web by serving as cues for herbivores to localize their host plants, or as a food source for microbes in both the rhizosphere and phyllosphere [8][9][10]. Owing to their multiple roles in plant ecology and advances in the real-time detection of trace gases (e.g., [11,12]), the study of VOCs that are emitted by crop plants has received increasing attention in the field of agroecology and crop protection. Provided that the emitted VOCs can be unequivocally identified and quantitatively measured without disturbing the actual physiological status of the plants, the online monitoring of the volatile metabolome represents a valuable non-invasive tool for early stress detection and survey of variation in plant fitness and phenology [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant VOCs also affect the food web by serving as cues for herbivores to localize their host plants, or as a food source for microbes in both the rhizosphere and phyllosphere [8][9][10]. Owing to their multiple roles in plant ecology and advances in the real-time detection of trace gases (e.g., [11,12]), the study of VOCs that are emitted by crop plants has received increasing attention in the field of agroecology and crop protection. Provided that the emitted VOCs can be unequivocally identified and quantitatively measured without disturbing the actual physiological status of the plants, the online monitoring of the volatile metabolome represents a valuable non-invasive tool for early stress detection and survey of variation in plant fitness and phenology [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Greenhouse crops are particularly suitable for this application, due to the lower and more constant air exchange than in the field, which favors the accumulation of trace gases in the air to values that are distinguishable from the background [16]. In recent years, several pilot studies on tomato have proven the potential usefulness of VOC monitoring, but also revealed limitations and obstacles to overcome [11,[17][18][19][20]. One prerequisite for a successful application is a sound knowledge of the natural variability of VOC release under non-stressed conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been reported on the use E-nose devices for plant-defense-related VOC monitoring, such as: (i) diagnosing Aphid-stressed tomato plants by first using GC-MS and identifying the VOCs emitted by the plant under stress including linalool, carveol, and nonane 2,2,4,4,6,8,8-heptamethyl and enhanced some terpene compounds (e.g., caryopllyllene). Next, commercial E-nose devices were employed and a PCA-based algorithm was developed for portable VOC recognition with a classification accuracy of 86.7% [160]; (ii) application of E-nose for diagnosing grapevine crown gall disease (caused by Agrobacterium vitis) [169], where infected grapevine rootstock was sampled in glass tubes overnight and target VOCs were determined using HS-SPME coupled GC-MS. Next, commercial E-nosed devices were employed and VOC data analysis was performed using PCA and linear discriminant analysis (LDA). An accuracy of 83.3% was achieved; (iii) an early detection of bacterial disease (fire blight caused by Erwinia amylovora and blossom blight caused by Pseudomonas syringae) in apple plants by monitoring VOC profiles [170], where the possible markers were identified using GC-MS and PTR-MS, while the application of commercial E-nose devices were assessed for portable operation demonstrating an accuracy of 75% using LDA-based data analysis.…”
Section: Et/vocs Detection Methods For Monitoring Biotic Stress In Plantsmentioning
confidence: 99%
“…Cui diagnosed greenhouse tomato plants infested by aphids in the early stages. New volatile organic compounds (linalool, carveol, and nonane (2,2,4,4,6,8,8-heptamethyl)) indicated aphid invasion on tomato plants (111). Quartz microbalance and mass spectrometry -based electronic noses are used to monitor the aroma profiles of two tomato varieties (Tradiro and Clotilde) during shelf-life conditions.…”
Section: Fruits and Vegetablesmentioning
confidence: 99%